The poetry of Atgimimas. Who Called the Nation and Who Led it? - Rėklaitytė, Akvilė (Colloquia, 2021)
The author of the article focuses on the time of the Reform Movement of Lithuania, Sąjūdis, when around 1987-1990 the Soviet Union began to fall apart and Lithuania was granted an opportune moment to seek political independence. In Lithuania, the Soviet ruling elite tried to exclude dissidents, who were more active in politics; therefore intellectuals, writers, and artists formed the vanguard of the movement for freedom. A review of documentary material from the time has revealed the important role of poetry. The article explores the poetic discourse of the years of Atgimimas, i.e. poems published in official and illegal publications, and analyses their poetics (themes, stylistics, and imagery). It aims to verify whether poetry was the “leader” of the Sąjūdis discourse, as many people who remember the movement testify. The research shows that during the political liberation of the state, poetry as an independent field of art had been in crisis. Instead of creating a distinctive aesthetic world and language, it illustrated the changes taking place in society, trying to keep up with historical events. Memoirs and journalism, which satisfied the public’s need for the direct talk about the realities, became the real leader of the discourse.
Keywords: Atgimimas; poetic discourse; poetic imagery; Lithuanian nation; history; memoirs; journalism